Advancements in Cellulose-Based Superabsorbent Hydrogels: Sustainable Solutions across Industries - Hossein Omidian; Arnavaz Akhzarmehr; Sumana Dey Chowdhury (Gels, 2024)
The development of superabsorbent hydrogels is experiencing a transformative era across industries. While traditional synthetic hydrogels have found broad utility, their non-biodegradable nature has raised environmental concerns, driving the search for eco-friendlier alternatives. Cellulose-based superabsorbents, derived from sustainable sources, are gaining prominence. Innovations include biodegradable polymer hydrogels, natural cellulose-chitosan variants, and cassava starch-based alternatives. These materials are reshaping agriculture by enhancing soil fertility and water retention, serving as potent hemostatic agents in medicine, contributing to pollution control, and providing eco-friendly construction materials. Cellulose-based hydrogels also offer promise in drug delivery and hygiene products. Advanced characterization techniques aid in optimizing their properties, while the shift towards circular economy practices further highlights sustainability. This manuscript provides a comprehensive overview of these advancements, highlighting their diverse applications and environmental benefits.